Tanggung Gugat Pelaku Usaha Obat Batuk Yang Merugikan Konsumen - Joy Valentine Tamaela; Theresia Louize Pesulima; Roulinta Yesvery Sinaga (Faculty of Law Universitas Pattimura, 2026)
The circulation of liquid cough medicine is common; unfortunately, there are cases of contaminated cough medicines that are unfit for consumption, causing harm to consumers. According to Law Number 8 of 1999 on Consumer Protection Article 4 Paragraph (3) regarding consumer rights, business actors who sell and produce liquid cough medicine are obliged to provide information on the composition and usage on the product packaging. However, there have been instances where contaminated liquid cough medicine provided a composition that did not comply with the standard composition of genuine liquid cough medicine, resulting in the provision of incorrect information.This research employs normative juridical legal research, examining legal principles and concepts as well as legislation. The research method involves primary, secondary, and tertiary legal materials, using statutory and conceptual approaches, and data collection techniques and legal analysis to address the issues.The research results indicate that responsibility in this case focuses more on fulfilling consumer rights and the obligations of business actors in the case of liquid cough medicine. The legal protection provided aims to ensure that consumer rights are not violated by business actors, in accordance with Article 1 Paragraph 1 of the Consumer Protection Act. If issues such as the one raised by the author occur, business actors must prioritize honesty and consumer safety, and comply with regulations regarding the rights and obligations between business actors and consumers.Legal protection for the involved parties can be implemented through legislation as a form of preventive legal protection, and also through repressive legal protection in the form of alternative dispute resolution or civil lawsuits in court. The government must also be more stringent in imposing sanctions on business actors who commit fraud. Thus, preventive and repressive measures can work in tandem to ensure consumer rights are protected and business actors are held accountable for their products.